Why is this financial crisis occurring? How to respond to it? - Daniel Daianu; Laurian Lungu (Transformation, Integration and Globalization Economic Research (TIGER), 2008)
A combination of cyclical and structural factors has lead to a situation which could threaten financial stability worldwide. As the current financial turmoil is unfolding it becomes clearer that the effects of the initial sub-prime crisis, which originated in the US, are spreading across other asset markets worldwide, increasing the likelihood of a global credit crunch and an economic downturn. In the light of these developments there is a need for the implementation of strategies for action. This paper focuses on structural causes of the current crisis and on policy issues such as enhancing transparency, resolving conflicts of interest, incentives structures in the financial industry and, not least, improving the existing regulatory and supervisory frameworks.
Keywords: G18; G28; 330; Finanzmarkt; Finanzkrise; Finanzprodukt; Unternehmenspublizität; Aufsichtsbehörde; Welt